Challenges and Opportunities in Implementing Renewable Energy - Deed, Ahmed; Al-Ghabera, Hassan; Ahmed, Rania Hassan; Youssef, Mariam; Mahmood, Abbas (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This research explores the possibilities of renewable energy, especially solar and wind energy, as a viable solution to Iraq's persistent energy crisis. Iraq, a nation with a historical reliance on oil and gas, is now experiencing significant power shortages and infrastructure issues due to extended conflict. This research employs a mixed-methods strategy—integrating expert interviews, public and industry surveys, along with comparative case studies from Morocco and Tunisia—to uncover both opportunities and challenges in the deployment of renewable energy systems. The results indicate a substantial potential for harnessing solar and wind energy while also emphasizing major challenges, such as insufficient infrastructure, unstable policies, and reduced investment. To address these challenges, the research highlights the importance of robust government dedication, infrastructure improvement, and increased involvement from the private sector. Moreover, cultural and economic contexts should be considered for successful implementation. The study finds that a comprehensive and inclusive national strategy is crucial for incorporating renewable energy into Iraq’s energy ecosystem. Additional research is recommended to evaluate project-specific viability, policy frameworks, and the effects of global collaboration on speeding up Iraq’s shift to renewable energy